2018
DOI: 10.7554/elife.43022
|View full text |Cite
|
Sign up to set email alerts
|

Random-sequence genetic oligomer pools display an innate potential for ligation and recombination

Abstract: Recombination, the exchange of information between different genetic polymer strands, is of fundamental importance in biology for genome maintenance and genetic diversification and is mediated by dedicated recombinase enzymes. Here, we describe an innate capacity for non-enzymatic recombination (and ligation) in random-sequence genetic oligomer pools. Specifically, we examine random and semi-random eicosamer (N20) pools of RNA, DNA and the unnatural genetic polymers ANA (arabino-), HNA (hexitol-) and AtNA (alt… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0
9

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 46 publications
(63 citation statements)
references
References 83 publications
3
49
0
9
Order By: Relevance
“…These findings are similar to those observed by Carrierio, and Damha (9) in which the G pT ligation site gave 10% yield, while T pT site gave 66% yield, and others (20,21), that have also found that pyrimidinepyrimidine base flanking is better than other base flanking compositions. average of two or three independent experiment replicates; with error bars representing the range of values measured.…”
Section: Influence Of Nick-site Flanking Base Pairs On Ligation Initisupporting
confidence: 90%
“…These findings are similar to those observed by Carrierio, and Damha (9) in which the G pT ligation site gave 10% yield, while T pT site gave 66% yield, and others (20,21), that have also found that pyrimidinepyrimidine base flanking is better than other base flanking compositions. average of two or three independent experiment replicates; with error bars representing the range of values measured.…”
Section: Influence Of Nick-site Flanking Base Pairs On Ligation Initisupporting
confidence: 90%
“…Here, we constructed and analyzed an RNA-based catalytic reaction model under prebiotically possible template-directed recombination and ligation. These modes of reproduction would have been more accessible to emergent polymeric pre-life than template-directed replication [17,18]. Using this system, we showed that at least in a subset of RNA population, sequence diversity within the population is a key factor to trigger RNA reproduction through iterative reactions.…”
Section: Discussionmentioning
confidence: 99%
“…These reactions are nearly energy-neutral but potentially irreversible if driven by the formation of stable secondary structures, and hence are prebiotically facile. Recombination of RNA oligomers has been recently demonstrated to occur readily, by a number of mechanisms [17,18]. The products could serve as a template for reactions that in turn catalyze their own production (i.e., autocatalytic reproduction).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the transition scenario toward existence of a sustainable replicase may be revised by considering different polymer generation processes anterior to the replicase regime. Polymer generation could have been enhanced by catalysis of polymerization ( Hazen and Sverjensky, 2010 ), ligation ( Mutschler et al., 2018 ), or recombination ( Blokhuis and Lacoste, 2017 ), as well as by size selection ( Mizuuchi et al., 2019 ). An alternative is that autocatalytic sets could have preceded template-based replication and biased polymer populations toward longer and more functional sequences ( Vasas et al., 2012 ).…”
Section: Refining and Revising The Replicase Scenariomentioning
confidence: 99%